Siting and capacity configurations of static transfer switches for three-phase unbalance governance in rural distribution networks: a bi-level optimization programme - Zhang, Jiguo; Jia, Keyin; Feng, Jun; Hao, Chenggang; Zheng, Shiyang; Shao, Junyan; Chen, Houhe (Frontiers in Energy Research, 2025)
Distributed Static Transfer Switch (STS) unlocks the potential to mitigate three-phase unbalances via the regulation of the load phase sequence within the system. However, the conventional solution is an unwise operation with high investment and inefficiency, constraining the deployment at scale. To address these challenges, this paper develops an innovative solution for the siting and capacity optimization of STS in rural distribution networks incorporating photovoltaic and energy storage systems (PESS). This optimization process is abstracted as a bi-level model of the strategy. Firstly, we develop an optimization upper-layer highlight on minimizing investment and maintenance costs for STS, taking into account branch loss reduction and three-phase unbalance mitigation. Secondly, we formulate a lower-layer optimization model with the mission of minimizing the three-phase unbalance in daily operation within the rural distribution network, taking into account the participation of PESS. Thirdly, the hyperparameter alternating iteration (HAI) method is leveraged to calculate the bi-level optimal planning and operation model, iteratively refining the STS planning solution. Finally, we present an illustrative case study of a three-phase distribution system via the IEEE-13 benchmark. The results demonstrate that the proposed bi-level optimization model effectively mitigated three-phase unbalance in rural distribution networks and minimized the planning cost for STS, thus offering a more cost-effective and efficient solution.